HUBUNGAN ANTARA KEDISIPLINAN SISWA DENGAN HASIL BELAJAR PADA PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA KELAS VIII SMP NEGERI 2 TELUKJAMBE BARAT - Mardhani Imaduddin; Rahmat Iqbal; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the relationship between student discipline and learning outcomes in physical education sports and health learning for class VIII students of SMP Neger 2 Telukjambe Barat. This research uses quantitative with correlation research methods using questionnaires. The research sample was class VIII students totaling 85 students. This study aims to determine the relationship between student discipline using a questionnaire and learning outcomes using the last semester report card scores. Data analysis techniques using product moment correlation techniques. The results obtained showed that if student discipline with learning outcomes in learning physical education sports and health as evidenced by the Significance value is 0.001 <0.05. These results can be interpreted that there is a relationship between student discipline and learning outcomes in learning physical education sports and health in class VIII students of SMP Negeri 2 Telukjambe Barat. And has a correlation of 0.377 and obtained a coefficient of determination R Square of 0.142 which implies that the influence of the student discipline variable with the learning outcomes variable is 14.2%.